BLOOD PRESSURE VARIABILITY ASSESSED WITH OFFICE, HOME AND AMBULATORY MEASUREMENTS BEFORE AND AFTER ANTIHYPERTENSIVE DRUG TREATMENT: THE REVERENT TRIAL. (June 2022) - Kyriakoulis, Konstantinos; Kollias, Anastasios; Bilo, Grzegorz; Soranna, Davide; Liu, Chang-Yuan; Pengo, Martino; Zambon, Antonella; Zhang, Wei; Wang, Jiguang; Stergiou, George; Parati, Gianfranco
Abstract : Objective: Blood pressure (BP) variability (BPV) can be assessed using office (OBP), home (HBP) and ambulatory BP (ABP) measurements. In this analysis BPV indices derived using all the three methods were compared before and after 10 weeks of antihypertensive drug treatment. Design and method: Untreated hypertensives (or treated after washout period) with elevated BPV (systolic HBP standard deviation [SD] > 7 mmHg and/or systolic daytime ABP SD > 12 mmHg), were nalysedd to ramipril 10 mg or nifedipine gastrointestinal therapeutic system (GITS) 30 mg once daily, in the context of a multicenter 10-week, prospective, nalysedd, open-label, blinded-end point study. BPV was assessed using SD and coefficient of variation (CV) [weighted SD (wSD) and weighted CV (wCV) for 24h-ABP variability) of individual measurements. Results: Data from 146 participants from three research centers (Athens, Milan, Shanghai) were nalysed (mean age 53 ± 10 [SD] years, males 60%, baseline systolic OBP, HBP and 24h-ABP 143 ± 10, 138 ± 10, and 143 ± 10 mmHg, respectively). Systolic CV assessed by HBP was decreased with treatment, by OBP was unchanged and by ABP increased (p < 0.05). HBP and ABP (not OBP) variability indices presented weak to moderate correlation, which was consistent before and after treatment (Table). HBP and ABP (not OBP) variability indices presented slight to fair agreement in detecting participants with high systolic BPV (top quartile of respective distribution) both before and after treatment (kappa statistic range 0.12–0.27). Conclusions: These data showed a moderate association between out-of-office (but not office) BPV indices both before and after administering BP lowering treatment, with reasonable agreement in detecting individuals with high BPV. Out-of-office BP measurements provide more similar BPV information than office measurements, both before and after administering antihypertensive drug treatment.